Effects of fatigue on the in vivo kinematics and kinetics of talocrural and subtalar joint during landing - Luo, Ye; Li, Zhuman; Hu, Mengling; Zhang, Ling; Li, Feng; Wang, Shaobai (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Fatigue can affect the ankle kinematic characteristics of landing movements. Traditional marker-based motion capture techniques have difficulty in accurately obtaining the kinematics of the talocrural and subtalar joints. This study aimed to investigate the effects of fatigue on the talocrural and subtalar joints during the landing using dual fluoroscopic imaging system (DFIS). Methods: This study included fourteen healthy participants. The foot of each participant was scanned using magnetic resonance imaging to create 3D models. High-speed DFIS was used to capture images of the ankle joint during participants performing a single-leg landing jump from a height of 40 cm. Fatigue was induced by running and fluoroscopic images were captured before and after fatigue. Kinematic data were obtained by 3D/2D registration in virtual environment software. The joint kinematics in six degrees of freedom and range of motion (ROM) were compared between the unfatigued and fatigued conditions. Results: During landing, after the initial contact with the ground, the main movement of the talocrural joint is extension and abduction, while the subtalar joint mainly performs extension, eversion, and abduction. Compared to unfatigued, during fatigue the maximum medial translation (1.35±0.45mm vs 1.86±0.69mm, p=0.032) and medial-lateral ROM (3.19±0.60mm vs 3.89±0.96mm, p=0.029) of the talocrural joint significantly increased, the maximum flexion angle (0.83±1.24°vs 2.11±1.80°, p=0.037) of the subtalar joint significantly increased, and the flexion- extension ROM (6.17±2.21° vs 7.97±2.52°, p=0.043) of the subtalar joint significantly increased. Conclusion: This study contributes to the quantitative understanding of the normal function of the talocrural and subtalar joints during high-demand activities. During landing, the main movement of the talocrural joint is extension and abduction, while the subtalar joint mainly performs extension, eversion, and abduction. Under fatigue conditions, the partial ROM of the talocrural and subtalar joints increases.